2006
DOI: 10.1177/0363546505279911
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Provocative Tests for Superior Labral Anterior Posterior Lesions

Abstract: The authors' results contradict the current literature regarding provocative testing for both stable and unstable superior labral lesions. There is no single maneuver that can accurately diagnose superior labral anterior posterior lesions; arthroscopy remains the standard by which to diagnose such lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
67
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 26 publications
2
67
0
Order By: Relevance
“…The researchers could have blinded the surgeons to the findings of the clinical testing, which would have improved the paper's overall quality, but in the population investigated it appears an accurate test. However, findings from other authors 12,31,35,36,41,47 investigating the same test (TABLE 6), including higher quality papers, did not confirm this accuracy.…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…The researchers could have blinded the surgeons to the findings of the clinical testing, which would have improved the paper's overall quality, but in the population investigated it appears an accurate test. However, findings from other authors 12,31,35,36,41,47 investigating the same test (TABLE 6), including higher quality papers, did not confirm this accuracy.…”
mentioning
confidence: 79%
“…The active compression test 39 was investigated by 8 other authors 12,24,30,[34][35][36]41,47 other than O'Brien et al, 39 with none reporting values similar to those reported in the original paper.…”
mentioning
confidence: 96%
See 3 more Smart Citations